2014
DOI: 10.1371/journal.pone.0090503
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Psychological Distress following War in the Former Yugoslavia: The Role of Interpersonal Sensitivity

Abstract: While high prevalence rates of psychological symptoms have been documented in civilian survivors of war, little is known about the mechanisms by which trauma exposure might lead to poor psychological outcomes in these populations. One potential mechanism that may underpin the association between war-related traumatic experiences and psychopathology is interpersonal sensitivity. In the current study, we applied structural equation modeling to investigate the impact of interpersonal sensitivity on posttraumatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
18
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…In the context of the war-affected youth, some of whom perpetrated horrendous atrocities against the civilian population to which they have been reintegrated, it has been defined as sensitivity to perceived or actual behaviors and feelings of others toward them that may define their mental health outcomes. Subsequent studies have reported that interpersonal sensitivity is linked to exposure to traumatic experiences, including war trauma ( Hauff & Vaglum, 1994 ; Nickerson, Priebe, Bryant, & Morina, 2014 ), with exposure to war often associated with higher levels of interpersonal sensitivity ( Hagenaars, Fisch, & van Minnen, 2011 ; Nickerson et al, 2014 ). Furthermore, interpersonal sensitivity has been linked to negative mental health outcomes, including PTSD, depression, and anxiety ( Hauff & Vaglum, 1994 ; Nickerson et al, 2014 ).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In the context of the war-affected youth, some of whom perpetrated horrendous atrocities against the civilian population to which they have been reintegrated, it has been defined as sensitivity to perceived or actual behaviors and feelings of others toward them that may define their mental health outcomes. Subsequent studies have reported that interpersonal sensitivity is linked to exposure to traumatic experiences, including war trauma ( Hauff & Vaglum, 1994 ; Nickerson, Priebe, Bryant, & Morina, 2014 ), with exposure to war often associated with higher levels of interpersonal sensitivity ( Hagenaars, Fisch, & van Minnen, 2011 ; Nickerson et al, 2014 ). Furthermore, interpersonal sensitivity has been linked to negative mental health outcomes, including PTSD, depression, and anxiety ( Hauff & Vaglum, 1994 ; Nickerson et al, 2014 ).…”
mentioning
confidence: 99%
“…Subsequent studies have reported that interpersonal sensitivity is linked to exposure to traumatic experiences, including war trauma ( Hauff & Vaglum, 1994 ; Nickerson, Priebe, Bryant, & Morina, 2014 ), with exposure to war often associated with higher levels of interpersonal sensitivity ( Hagenaars, Fisch, & van Minnen, 2011 ; Nickerson et al, 2014 ). Furthermore, interpersonal sensitivity has been linked to negative mental health outcomes, including PTSD, depression, and anxiety ( Hauff & Vaglum, 1994 ; Nickerson et al, 2014 ). Responses such as lack of trust and interpersonal insensitivity may be adaptive, albeit in the short run, in the aftermath of war, especially where stigma and poor community relations trigger traumatic reminders and threats to war survivors ( Nickerson et al, 2014 ).…”
mentioning
confidence: 99%
See 3 more Smart Citations